Robust speech enhancement using amplitude spectral estimator - Abdul Rahman, Abdul Wahab; Chong, Tan Eng; Abut, Huseyin (2000)
This paper focuses on a class of speech enhancement systems using the amplitude spectral estimates of noisy speech and noise to drive a Wiener filter to suppress simultaneously the ensemble of degradations picked up by microphones. A simple stereo microphone set with left and right channels can be used to provide enough separation that unwanted signals can be reduced significantly to yield acceptable quality speech signal for handsfree telephony application in a vehicular environment. A generalized transform approach was introduced and experimental results show great potential when using the DCT as alternatives to the traditional Fourier transform approach to derive the amplitude spectral estimates of the corrupted speech signals and the noise process.